2009
DOI: 10.1007/s00425-009-0950-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic evaluation of pulsed electric field-induced stress on potato tissue

Abstract: Metabolite profiling was used to characterize stress responses of potato tissue subjected to reversible electroporation, providing insights on how potato tissue responds to a physical stimulus such as pulsed electric fields (PEF), which is an artificial stress. Wounded potato tissue was subjected to field strengths ranging from 200 to 400 V/cm, with a single rectangular pulse of 1 ms. Electroporation was demonstrated by propidium iodide staining of the cell nucleae. Metabolic profiling of data obtained through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…Moderate-intensity pulsed electric fields (MIPEF) permeabilise tissue structures, thus improving intracellular metabolite extraction (SolivaFortuny et al, 2009) and enhancing drying efficiency (De Vito et al, 2008). Metabolic responses of plant cells (Cai et al, 2011) and tissues (Galindo et al, 2009) upon the application of MIPEF have been studied. The analysis of potato demonstrated that, 24 h after the application of MIPEF, tissue metabolism showed MIPEF-specific stress responses, characterised by changes in the hexose pool that may involve starch and ascorbic acid degradation (Galindo et al, 2009).…”
Section: Application Of Pulsed Electric Field Processing In Food Indumentioning
confidence: 99%
See 2 more Smart Citations
“…Moderate-intensity pulsed electric fields (MIPEF) permeabilise tissue structures, thus improving intracellular metabolite extraction (SolivaFortuny et al, 2009) and enhancing drying efficiency (De Vito et al, 2008). Metabolic responses of plant cells (Cai et al, 2011) and tissues (Galindo et al, 2009) upon the application of MIPEF have been studied. The analysis of potato demonstrated that, 24 h after the application of MIPEF, tissue metabolism showed MIPEF-specific stress responses, characterised by changes in the hexose pool that may involve starch and ascorbic acid degradation (Galindo et al, 2009).…”
Section: Application Of Pulsed Electric Field Processing In Food Indumentioning
confidence: 99%
“…Metabolic responses of plant cells (Cai et al, 2011) and tissues (Galindo et al, 2009) upon the application of MIPEF have been studied. The analysis of potato demonstrated that, 24 h after the application of MIPEF, tissue metabolism showed MIPEF-specific stress responses, characterised by changes in the hexose pool that may involve starch and ascorbic acid degradation (Galindo et al, 2009). MIPEF-induced stresses could include a burst of ROS, which are endogenous signal components required for synthesis of secondary metabolites, such as polyphenols or carotenoids, which are known to be part of the defence response of plants to stress (Shohael et al, 2006).…”
Section: Application Of Pulsed Electric Field Processing In Food Indumentioning
confidence: 99%
See 1 more Smart Citation
“…It is a research tool that can detect and monitor unidentified compounds as well as identified metabolites that play important roles in metabolism and physiology (Kaplan et al, 2004). For example metabolite profiling was used to characterize stress responses of potato tissue subjected to reversible electroporation, providing insights on how potato tissue responds to a physical stimulus such as pulsed electric fields (PEF), which is an artificial stress (Galindo et al, 2009). …”
Section: Metabolomicsmentioning
confidence: 99%
“…Wounded potato tissue was subjected to field strengths ranging from 200 to 400 V/cm, with a single rectangular pulse of 1 ms. Electroporation was demonstrated by propidium iodide staining of the cell nuclei. Metabolic profiling of data obtained through GC-(TOF)-MS and UPLC-(TOF)-MS complemented with orthogonal projections to latent structures clustering analysis showed that 24 h after the application of pulsed electric fields potato (PEF)-specific responses in the potato metabolism were characterized by the changes in the hexose pool that may involve starch and ascorbic acid degradation [89].…”
Section: Pulsed Electric Field-induced Stressmentioning
confidence: 99%